Health, Medicine and Society - Habarurema, Gad Samuel (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2021)
This paper argumentatively analyzed and discussed health, medicine and society. This paper is divided into five main sections that cover health and introduce the natural sciences basically biology and chemistry which provides an important foundation for the understanding of health, development of possible medical interventions and public health programs in the society, medicine with some diseases because in the primary function of medicine is to cure or control a disease and section of society which is completely related to public health in order to understand society in the field of public health. The other four sections are general discussion that introduces this paper, the general discussion that links health to public health, medicine to public health and links society to public health. Other sections are significance, conclusion and the bibliography. This paper defines health as a state of complete physical, mental, and social well-being and not basically the absence of infirmity or diseases (WHO, 2005). Medicine is defined as science and practices of establishing the diagnosis, prognosis, treatment, and prevention of disease. While, society is defined as a group of people that are involved in durable social interaction, or a big social group that shares the equal spatial or social territory, typically subject to the same political authority and dominant cultural expectations. Thus, this paper discusses these three mains components and related them to public health.